2018
DOI: 10.1016/j.ejca.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of prolonged benefit from palbociclib plus fulvestrant in women with endocrine-resistant hormone receptor–positive/human epidermal growth factor receptor 2–negative metastatic breast cancer in PALOMA-3

Abstract: Background: The addition of palbociclib to fulvestrant improved clinical outcomes over placebo-fulvestrant in endocrine-pretreated metastatic breast cancer (MBC) patients in PALOMA-3. Here, we examined factors predictive of long-term benefit. Methods: Premenopausal-peri/postmenopausal patients with endocrine-resistant, hormone receptorepositive (HRþ)/human epidermal growth factor receptor 2enegative MBC were randomised 2:1 to fulvestrant (500 mg) and either palbociclib (125 mg/d; 3/1 schedule; n Z 347) or plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 25 publications
8
42
0
Order By: Relevance
“…3, where the primary samples were collected post-endocrine therapy and had already developed an ESR1 alteration. ESR1 mutations arise due to prolonged treatment with tamoxifen and aromatase inhibitors; however, retrospective analysis of the PALOMA-2 and PALOMA-3 studies found that patients treated with a selective oestrogen degrader either alone or in combination with CDK4/6 inhibitors also showed development of ESR1 mutations [37][38][39]. As expected, TP53 alterations were the most prevalent across all samples.…”
Section: Discussionmentioning
confidence: 55%
“…3, where the primary samples were collected post-endocrine therapy and had already developed an ESR1 alteration. ESR1 mutations arise due to prolonged treatment with tamoxifen and aromatase inhibitors; however, retrospective analysis of the PALOMA-2 and PALOMA-3 studies found that patients treated with a selective oestrogen degrader either alone or in combination with CDK4/6 inhibitors also showed development of ESR1 mutations [37][38][39]. As expected, TP53 alterations were the most prevalent across all samples.…”
Section: Discussionmentioning
confidence: 55%
“…Additionally, patients with ESR1 mutations treated with the combination had a better outcome than patients with ESR1 mutations receiving fulvestant monotherapy, suggesting that mutational status had a prognostic but not predictive value. In further support of their prognostic role, baseline tumor ESR1 mutation rates were found to be lower among long-term responders in both PALOMA-3 trial arms [55]. A recent analysis of plasma samples collected at baseline, cycle 1 day 15, and at the end of treatment (EOT) from patients recruited to PALOMA-3 showed that ESR1 mutations had a greater suppression by fulvestrant plus placebo compared to PIK3CA mutations but does not predict improvement in PFS on fulvestrant [56].…”
Section: Esr1 Mutations In Patients Treated With Cdk4/6 Inhibitorsmentioning
confidence: 83%
“…A high PR expression was associated with prolonged benefit in patients receiving either palbociclib plus fulvestrant or placebo plus fulvestrant in the Paloma-3 trial, independently of the treatment arm [ 25 ]. Furthermore, a recent review and meta-analysis by Ramos-Esquivel et al [ 26 ] showed that the addition of CDK4/6i significantly improved PFS, overall response rate and clinical benefit regardless of age, performance status, and disease setting but not race.…”
Section: Discussionmentioning
confidence: 99%